PENGARUH CAR, LDR DAN NIM TERHADAP ROA PADA PERUSAHAAN SUBSEKTOR PERBANKAN - Listiawati Listiawati; Irwan Sukmana; Siska Amelia (Universitas Bina Bangsa, 2021)
The banking sector plays an important role in moving the wheels of a country's economy. The entire banking sector has a goal in increasing profitability. Profitability is used as a basis for seeing the company's ability to earn profits within a certain period. The level of profitability to measure profitability one of which uses the return on asset approach. The purpose of this study is to study and analyze the factors that affect profitability. The research method used is descriptive method with quantitative research type. The data used are secondary data on CAR, BOPO, LDR, NIM and ROA sub-sector listed on the indoinesio stock exchange. The results show that LDR are not significant on ROA, but CAR and NIM have a significant effect on ROA